2022
DOI: 10.1186/s13213-022-01675-7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of epiphytic bacterial communities on male and female Porphyra haitanensis

Abstract: Purpose To study the structure of the epiphytic bacterial community of the male and female Porphyra haitanensis, in order to explore the similarities and differences of epiphytic bacterial community structure between dioecious macroalgae. Methods Collection of male and female Porphyra haitanensis from the intertidal zone of Niushan Island, Fujian, China. Epiphytic bacteria were collected and studied, and the community composition and diversity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The results indicated that sex did not greatly affect epiphytic bacterial communities on S. thunbergii . The same result was observed in marine macroalga Agarophyton vermiculophyllum (Bonthond et al 2020 ) and P. haitanensis (Yang et al 2022 ) that showed the sex had only a negligible, statistically insignificant impact on the bacterial composition. However, we found that the relative abundance of some genera, indicative species, specific bacteria and predicted functions of epiphytic bacteria were different between male and female S. thunbergii .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The results indicated that sex did not greatly affect epiphytic bacterial communities on S. thunbergii . The same result was observed in marine macroalga Agarophyton vermiculophyllum (Bonthond et al 2020 ) and P. haitanensis (Yang et al 2022 ) that showed the sex had only a negligible, statistically insignificant impact on the bacterial composition. However, we found that the relative abundance of some genera, indicative species, specific bacteria and predicted functions of epiphytic bacteria were different between male and female S. thunbergii .…”
Section: Discussionsupporting
confidence: 70%
“…The differences of epiphytic bacteria on dioecious higher plants are better known; for example, the epiphytic bacterial communities in Populus cathayana rhizospheres differ between the sexes (Liu et al 2020 ). Additionally, some bacteria were differentially enriched on the male and female Porphyra haitanensis (Yang et al 2022 ). Epiphytic and specific bacterial communities associated with the sex of the macroalgae need further research.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of host plant sex on epiphytic bacterial communities has been verified in the higher plant Populus cathayana ( Liu et al, 2021 ). Additionally, some bacteria were differentially enriched on the male and female Porphyra haitanensis ( Yang et al, 2022 ). This study detected the differences in the diversity, specific taxa, and indicator species of the epiphytic bacterial communities, verifying that sex was a driving factor in the construction of the epiphytic bacterial community of S. thunbergii and its reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial communities of interleaf microorganisms of the higher plant Populus cathayana have been found to be influenced by sex ( Liu et al, 2021 ), with significant differences in the relative abundance at the genus level. Similarly, epiphytic bacterial communities of Porphyra haitanensis were also found to be influenced by the sex of the host plant ( Yang et al, 2022 ). However, there have been few studies related to dioecious macroalgae.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, sex can lead to differences in the morphology, structure and function of dioecious plants (Tang, 2020;Lu et al, 2021;Zeng et al, 2022), and there are also some differences in enzyme activity (Chen et al, 2020), secondary metabolites (Li et al, 2022) and endogenous hormone levels (Ge et al, 2021), but there have been few studies on sex differences in endophytic bacteria in plants. Some studies have revealed differences in epiphytic bacterial communities in plants of different sexes, such as in Populus cathayana (Liu et al, 2021), Sargassum thunbergii (Wang et al, 2022b), and Porphyra haitanensis (Yang et al, 2022). However, for marine macroalgae, whether sex has an impact on the assembly of endophytic bacterial communities is still unknown.…”
Section: Introductionmentioning
confidence: 99%